The Conflicts of Law in Islamic Banking Based on The Contracts Act 1950 and Evidence Act 1950 : Malaysian Position - Muhammad Hafiz, Mohd Shukri (Human Resource Management Academic Research Society (HRMARS), 2020)
In order to maintain and uphold the institution of Islamic banking for future generations, it is vital to resolve potential conflicts that are faced by the Islamic banking sector. Malaysia is currently facing legislative conflicts between Islamic law and civil law, even after more than 30 years since the establishment of Islamic banking. Several court cases have proven that there are many conflicting issues in the Malaysian Islamic banking sector, which have posed a challenge to the Islamic financial system in Malaysia. This article aims to construct a harmonized legal framework between Islamic law and civil law in regulating the industry of Islamic banking, particularly through the enforcement of the Contracts Act 1950 and the Evidence Act 1950. The type of research carried out for the purpose of this paper is doctrinal legal research. The data sources were gathered and analysed using content analysis and critical analysis methods. The results showed that there are some statutory provisions in the abovementioned statutes which are not compatible with the principles of Islamic banking. As such, several recommendations have been suggested in order to harmonize the legal conflicts as they occur in the statutory provisions. Lastly, the outcomes of this research are expected to assist the harmonization process of legislation together with the intention of facilitating the development of the Islamic banking industry in Malaysia.